Finnish new variant of Chlamydia trachomatis escaping detection in the Aptima Combo 2 assay also present in Örebro County, Sweden, May 2019 - Unemo, Magnus (Euro Surveill, 2019)
We identified the first two cases of the Finnish new variant of Chlamydia trachomatis (F-nvCT) beyond Finland in two clinical urogenital specimens in Örebro County, Sweden. These Aptima Combo 2 assay-negative specimens were Aptima Chlamydia trachomatis (CT) assay positive and had the characteristic C1515T mutation in the 23S rRNA gene. From 22 March to 31 May 2019, 1.3% (2/158) of the CT-positive cases in Örebro County were missed because of the F-nvCT. International awareness, investigations and actions are essential.